Website Quality To Increase Franchise Marketing Performance Excellent - Halim, Erwin; Kurniawan, Yohannes (ComTech: Computer, Mathematics and Engineering Applications, 2016)
According to Indonesia Association of Service Provider (APJII) survey in 2014, the internet user in Indonesia increased up to around 88 million. This number expresses that the use of the internet to seek business franchise information will increase as well. The increase of internet using should be followed by the quality of franchisor's website. The franchisor's website will relate to system quality, information quality and service quality (DeLone and McLean, 2003). This research uses SEM LISREL to see the loading factors of each indicator impact in variables and website quality variables impact to intention to purchase franchise. The result shows that all variables (System quality, Information Quality, and Service Quality) give significant impact to dependent variable Website Quality.